2021
DOI: 10.1002/er.7502
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study: Design and implementation of a floating photovoltaic system for hydrogen production

Abstract: Summary In this study, lab‐made modified graphite cathodes were used to design and implement floating PV assisted alkaline electrolysis cell. The influence of temperature on PV performance was studied both experimentally and theoretically, and the PV module performance was investigated in floating as well as non‐floating modes. Power generation of floating PV panel and non‐floating PV panel at four different air temperatures was examined. Although there was no substantial improvement in power generation at 6°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 81 publications
(136 reference statements)
0
2
0
Order By: Relevance
“…It is observed that a lot of scientific studies have been conducted on the production of hydrogen gas through literature review [33][34][35][36][37][38]. Mert and her colleagues [39] designed different cathodes and produced hydrogen gas in an alkaline electrolysis system using electricity from a real hybrid system based on solar and wind energy, which was necessary for each cathode.…”
Section: Hydrogen Production and Its Contribution To The Green Economymentioning
confidence: 99%
“…It is observed that a lot of scientific studies have been conducted on the production of hydrogen gas through literature review [33][34][35][36][37][38]. Mert and her colleagues [39] designed different cathodes and produced hydrogen gas in an alkaline electrolysis system using electricity from a real hybrid system based on solar and wind energy, which was necessary for each cathode.…”
Section: Hydrogen Production and Its Contribution To The Green Economymentioning
confidence: 99%
“…The two servo systems in the system are the same and independent of each other [8]. Servo motor control has important practical significance for improving the control and tracking accuracy of photovoltaic power generation servo systems and ensuring the safe and stable operation of power systems [9]. However, a photovoltaic power generation servo control system has many unknown parameters, and the control is complex.…”
Section: Related Workmentioning
confidence: 99%